2022
DOI: 10.3389/fmed.2021.800943
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Vital Signs and Risk of In-Hospital Cardiac Arrest

Abstract: Background: Little is known about the trajectories of vital signs prior to in-hospital cardiac arrest (IHCA), which could explain the heterogeneous processes preceding this event. We aimed to identify clinically relevant subphenotypes at high risk of IHCA in the emergency department (ED).Methods: This retrospective cohort study used electronic clinical warehouse data from a tertiary medical center. We retrieved data from 733,398 ED visits over a 7-year period. We selected one ED visit per person and retrieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Previous research has already shown that accounting for differences in vital signs values between day and night may reduce alarm rate in various models at the general ward [ 24 ]. The next step in predictive modeling with continuous data is trend analysis, since changes of vital signs might be better predictors than single values [ 43 , 44 ]. Both model builders and hospital professionals should be aware however that a rise in heart rate and respiratory rate in the morning, or a rise of skin temperature in the evening, might not be a deteriorating trend at all, but rather a part of a physiological rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has already shown that accounting for differences in vital signs values between day and night may reduce alarm rate in various models at the general ward [ 24 ]. The next step in predictive modeling with continuous data is trend analysis, since changes of vital signs might be better predictors than single values [ 43 , 44 ]. Both model builders and hospital professionals should be aware however that a rise in heart rate and respiratory rate in the morning, or a rise of skin temperature in the evening, might not be a deteriorating trend at all, but rather a part of a physiological rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…Key considerations include aggregating vital signs [40], integrating contextual factors like signs/symptoms, patient circadian rhythm, and activity levels. Establishing baseline values preoperatively and assessing relative deviations from established trends in vital signs over time intervals [78], along with incorporating laboratory values, can bolster prediction models for clinical deterioration [79].…”
Section: Software Platforms For Trend Analysismentioning
confidence: 99%